Loudness perception deficits during altered and absent auditory feedback in Parkinson’s disease - Dona Anita Senthinathan; Scott G. Adams; Scott G. Adams; Scott G. Adams; Allyson D. Page; Allyson D. Page; Mandar Jog (Frontiers in Human Neuroscience)
Patients with Parkinson’s disease (PD) present with speech difficulties including abnormal speech intensity regulation. It is possible that the neural circuitry in speech may be unique and more complex compared to the other major motor symptoms. The current study aimed to provide a better understanding of the sensorimotor integration and loudness perception deficits in PD using an altered intensity feedback (AIF) paradigm. Twenty-six participants with PD and 26 neurologically healthy control participants completed a magnitude production task (normal loudness, 2× louder, 4× louder, and max loudness) while being presented with AIF and background noise. The task was repeated in complete masking noise and loudness perception ratings were obtained in all conditions (no noise and background noise). Results suggest that unlike previous studies in other sensorimotor domains, individuals with PD display a reduced reliance on auditory sensory feedback such that during a speech magnitude production task, their perception of those productions may rely less on the auditory sensory feedback being received. Loudness perception results in the absence of auditory feedback suggest a modulating effect of sensory feedback on somatosensation or sense of effort in PD.